2017
DOI: 10.1038/srep43113
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the role of gene mutations in myelodysplastic syndromes through a sequencing design involving a small number of target genes

Abstract: Novel sequencing designs are necessary to supplement the recognized knowledge of myelodysplastic syndrome (MDS)-related genomic alterations. In this study, we sequenced 28 target genes in 320 Chinese MDS patients but obtained 77.2% of recall factors and 82.8% of genetic abnormalities (including karyotype abnormalities). In addition to known relationships among mutations, some specific chromosomal abnormalities were found to link to specific gene mutations. Trisomy 8 tended to be linked to U2AF1 and ZRSR2 mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 31 publications
(74 reference statements)
3
42
0
1
Order By: Relevance
“…-7/del(7q) are remarkably coincident with SETBP1 mutations, which is confirmed by multiple independent studies (Fig. 4c) [30,45,57,61]. Isochromosome 17q (i(17q)) is also associated with SETBP1 mutations (54%) [45,48,57,62].…”
Section: Coordination With Additional Genetic Eventssupporting
confidence: 66%
“…-7/del(7q) are remarkably coincident with SETBP1 mutations, which is confirmed by multiple independent studies (Fig. 4c) [30,45,57,61]. Isochromosome 17q (i(17q)) is also associated with SETBP1 mutations (54%) [45,48,57,62].…”
Section: Coordination With Additional Genetic Eventssupporting
confidence: 66%
“…The purity (OD260/280 > 1.8) and concentration (50 ng per µl) of the gDNA met the sequencing requirements. Sequencing methods and statistical analysis are referred in our previous study 27 .…”
Section: Methodsmentioning
confidence: 99%
“…Investigation of MDS at the molecular level has increased our understanding of recurrently mutated pathways including those of RNA splicing, DNA methylation, transcription regulation and chromatin and histone modification. Multiple studies have now demonstrated the significance of somatic point mutations in MDS, in regards to overall and leukemic free survival . Accordingly, we and others have already started incorporating genetic information into clinical risk models in MDS .…”
Section: Discussionmentioning
confidence: 99%
“…The revised international prognostic scoring system (IPSS‐R) is currently the standard tool used to risk stratify MDS patients and is based on both clinical and cytogenetic data . Most recently, next‐generation sequencing (NGS) technology has enabled identification of mutations in MDS that adversely affect overall or leukemia‐free survival, including ASXL1 , TP53 , EZH2 , ETV6 , RUNX1 , WT1 , SRSF2 , IDH1 , IDH2 , DNMT3A , SETBP1 , CSF3R , and others . Several teams of investigators have now begun incorporating mutation information into clinical risk models; the most noteworthy in this regard was the Mayo Alliance prognostic model for MDS; in the particular study that included 685 molecularly‐annotated patients from the Mayo Clinic and the National Taiwan University Hospital, multivariable analysis identified monosomal karyotype (MK), “non‐MK abnormalities other than single/double del(5q),” RUNX1 and ASXL1 mutations, absence of SF3B1 mutations, age > 70 years, hemoglobin <8 g/dL in women or <9 g/dL in men, platelet count <75 × 10 9 /l and bone marrow blasts ≥10%, as predictors of inferior overall survival; subsequently, a four‐tiered risk model was devised, with median survivals of 85 months for low, 42 months for intermediate‐1, 22 months for intermediate‐2 and 9 months for high risk disease.…”
Section: Introductionmentioning
confidence: 99%